Pengaruh Modernisasi Sistem Administasi Perpajakan, Pemahaman Peraturan Perpajakan, dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi di KPP Pratama Semarang Barat - Maharani, Marcella; Utomo, Dwiarso; Durya, Ngurah Pandji Mertha Agung (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to empirically test whether the modernization of the tax administration system, the level of understanding of tax regulations, and tax sanctions have an influence on the compliance of individual taxpayers at KPP Pratama West Semarang in 2024. The method used includes quantitative data analysis by collecting information from taxpayers regarding understanding of regulations and application of sanctions. The data is processed by multiple regression analysis method using SPSS. The results of the analysis show: (1) Modernization of the tax administration system affects individual taxpayer compliance; (2) The level of understanding of tax regulations has no effect on individual taxpayer compliance; (3) Tax sanctions affect individual taxpayer compliance. The R Square value of 0.690 indicates that 69% of the variation in the dependent variable is explained by the independent variable, while 31% is influenced by other factors.